STRATEGIC CONSUMER EXPERIENCE OPTIMIZATION AS A PROFITABILITY DRIVER DURING ECONOMIC DOWNTURNS (NAU Journal of Technology and Vocational Education, 2026)
Economic recessions impose severe constraints on business profitability and customer retention, yet the dominant organisational response of cost reduction alone risks weakening the consumer relationships necessary for post-recession recovery. This paper advances the argument that strategic consumer experience optimisation offers a more sustainable pathway for maintaining profitability during economic downturns. The paper adopts a theoretical and advocacy-based approach, drawing on insights from behavioural economics, strategic marketing, and technology management. It synthesises existing literature to develop a recession-oriented framework for consumer experience management rather than presenting original empirical findings. Available evidence suggests that consumer behaviour during periods of economic stress may display recovery-oriented tendencies when supported by targeted experience interventions, although such patterns should be interpreted with caution given the limited scope of existing studies. Specifically, the paper argues that AI-driven personalisation can sustain service quality while managing operational costs, that cross-generational experience strategies are necessary to address diverse consumer responses, that real-time adaptation mechanisms enable timely organisational responses to shifting economic conditions, and that performance measurement systems must balance short-term financial pressures with long-term experience value. The paper challenges the assumption that economic recessions necessitate organisational retrenchment, proposing instead that such periods create opportunities for experience innovation and competitive differentiation. It calls on business leaders, policymakers, and technology providers to adopt proactive, customer-centred strategies that support both consumer satisfaction and long-term financial sustainability in uncertain economic conditions.
Keywords: Economic recession; Customer retention; Service quality management; profitability strategy; Digital transformation